The absorber in parametric and forced systems - Dinh, Nguyen Van (Vietnam Journal of Mechanics, 1980)
In this paper, we consider the action of the absorber in the parametric and forced system. If we connect the non-resonant absorber to examined system the frequency will be changed and the resonant oscillation disappears; the resonant absorber is governed by the well-known principle in self-excited system [5].